2011
DOI: 10.1089/hum.2010.140
|View full text |Cite
|
Sign up to set email alerts
|

AAV Delivery of Wild-Type Rhodopsin Preserves Retinal Function in a Mouse Model of Autosomal Dominant Retinitis Pigmentosa

Abstract: Autosomal dominant retinitis pigmentosa (ADRP) is frequently caused by mutations in RHO, the gene for rod photoreceptor opsin. Earlier, a study on mice carrying mutated rhodopsin transgenes on either RHO þ / þ or RHO þ /-backgrounds suggested that the amount of wild-type rhodopsin affected survival of photoreceptors. Therefore, we treated P23H RHO transgenic mice with adeno-associated virus serotype 5 (AAV5) expressing a cDNA clone of the rhodopsin gene (RHO301) that expressed normal opsin from the mouse opsin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
112
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(115 citation statements)
references
References 39 publications
2
112
1
Order By: Relevance
“…For example, the thoroughly studied P23H mutation in rhodopsin (a single amino acid substitution of proline at position 23 for histidine), frequently encountered in retinitis pigmentosa patients (2,3), was shown to cause rhodopsin misfolding and endoplasmic reticulum (ER) accumulation (4,5), ultimately resulting in an unfolded protein response and cell death (6,7). Protein misfolding is considered a therapeutic target in the ongoing clinical trial in which patients with retinitis pigmentosa are treated with valproic acid (http:// clinicaltrials.gov/ct2/show/study/NCT01233609), the substance suggested to act as a pharmacological chaperone for unfolded proteins (8,9).…”
mentioning
confidence: 99%
“…For example, the thoroughly studied P23H mutation in rhodopsin (a single amino acid substitution of proline at position 23 for histidine), frequently encountered in retinitis pigmentosa patients (2,3), was shown to cause rhodopsin misfolding and endoplasmic reticulum (ER) accumulation (4,5), ultimately resulting in an unfolded protein response and cell death (6,7). Protein misfolding is considered a therapeutic target in the ongoing clinical trial in which patients with retinitis pigmentosa are treated with valproic acid (http:// clinicaltrials.gov/ct2/show/study/NCT01233609), the substance suggested to act as a pharmacological chaperone for unfolded proteins (8,9).…”
mentioning
confidence: 99%
“…The notable retinal preservation reported by Jacobson et al (2013) suggests that LCA1 patients are good candidates for subretinal injection. The AAV serotypes used in proof-of-concept LCA1 studies, AAV5 and AAV8, have proven utility following subretinal injection in various mouse and dog models of photoreceptor-mediated disease (Min et al 2005;Alexander et al 2007;Boye et al 2010Boye et al , 2013Gorbatyuk et al 2010;Komaromy et al 2010;Mao et al 2011;Pang et al 2011Pang et al , 2012Yao et al 2011;Beltran et al 2012). Because transduction can vary across species, it is essential to evaluate vectors in a species as closely related to man as possible.…”
Section: Discussionmentioning
confidence: 99%
“…48 In situations where at least some of the disease phenotype results from reduced levels of wild-type protein, delivery of the wild-type gene in the absence of suppression of the mutant allele may potentially provide benefit. In this regard, Mao et al 49 have delivered the wildtype RHO gene to P23H Rho+/+ mice and obtained some histological and electroretinographic benefit at 6 months post-injection benefit. The thickness of the outer nuclear layer of treated eyes was 80% greater than of control eyes and A-and B-wave amplitudes were increased by 100% and 79%, respectively.…”
Section: Preclinical Studies Using Therapies Targeting the Primary Gementioning
confidence: 99%